Temporarily protected Syrians’ access to the healthcare system in Turkey: Changing policies and remaining challenges - Bilecen, Basak; Yurtseven, Dilara (Migration Letters, 2018)
The recent increase in the migratory flows of Syrian asylum-seekers has drawn attention to the causes and, more fundamentally, to the consequences of such mobility patterns in both the European Union and in Turkey. In this paper we explore the healthcare system in Turkey and, particularly, Syrians’ access to healthcare services. Bringing together the literature on healthcare and on mobility from conflict zones, this paper advances our understanding of the challenges in access to healthcare facilities faced by a vulnerable population – namely displaced persons from Syria living in Turkey. Based on an analysis of secondary literature and social policies, we observe three main challenges faced by Syrians in Turkey in accessing healthcare services: registration procedure, navigation of the system and language barriers.